A Discourse Analysis Of "Your Letters" On Readers' Forum In The Jakarta Post - Puspita Sari, Raih; , Dra. Malikatul Laila, M.Hum; , Dra. Siti Zuhriah Ariatmi, M.Hum (2015)
The aims of the study are explaining the discourse of "Your Letters" in term of grammatical cohesion and describing the elements configuring the discourse of "Your Letters". The objects to be analyzed are discourse aspects in "Your Letters" such as non-linguistic context and grammatical cohesion. The data are taken from discourses of "Your Letters" in the Jakarta Post published August 2014. In collecting data, the writer uses method of observation and documentation by applying techniques of collecting, reading, identifying, underlining and coding the data. The strategy to analyze the first aim is by referring to the theory of grammatical cohesion, while to analyze the second aim is by using non-linguistic context. The result of the research shows that the types of grammatical cohesion found in these discourses are 291 or 27, 85% of personal reference, 421 or 40, 29% of demonstrative reference, 3 or 0, 29% of nominal substitution, 21 or 2, 01% of nominal ellipsis, 77 or 7, 37% of adversative conjunction, 202 or 19, 33% of additive conjunction, 12 or 1, 15% of causal conjunction, and 18 or 1, 72% of temporal conjunction. Moreover, there are six elements to configure the sense of discourse of "Your Letters" that they are: 1) type of communicative event found are exposition, narration, argumentation, recount, discussion, description and news item; 2) the topic that can be seen from the title and the object told in the discourse; 3) the purpose of the event that related to the type of communicative event; 4) the setting of place and time; 5) the participants and their relationship; 5) the background knowledge.